Perspektywy widzenia – znaczenia przestrzeni miast w komiksach - Sęk-Iwanek, Matylda (Załącznik Kulturoznawczy, 2021)
The article strives to present select examples of urban observations and imaginaries present in comics. It draws attention to the way the city is perceived and presented in graphic novels, and how imaginary and existing spaces transcend. Furthermore, it touches on mediated sight and visuality. Lastly, it discusses comic reportage and its role in exploring the invisible.